ECONOMIC JUSTICE PERSPECTIVE ARTICLE 33 Of THE CONSTITUTION Of THE REPUBLIC Of INDONESIA IN 1945 AS THE ORIGINAL REPRESENTATION Of THE INDONESIAN ECONOMY - Riski Febria Nurita; Supriadi; I Gusti Ngurah Adnyana; Darmawati (OIKONOMIA: Journal of Economics and Management Science, 2024)
Article 33 of the 1945 Indonesian constitution amendment consisting of 5 paragraphs is a basic norm that makes economic policy the cornerstone of the direction of National Economic Policy. Article 33 of the 1945 Indonesian constitution which is then translated into laws and other legislation as a legal policy in terms of a more operational economy. Article 33 of the 1945 Indonesian constitution is a constitutional legal norm that is absolute and must not be violated by economic policy makers. Economic policy should refer to and should not be contrary to the Constitution so that economic policy makers should not make economic policies that are contrary to Article 33 of the 1945 Indonesian constitution